Distributional patterns of microplastics in sediment samples from coastal (Oslofjord, Norway) and deep (North-eastern Greenland Sea slope; Kveithola Trough, Barents Sea) marine environments - BRONZO, LAURA (Pisa University, 2020)
Versatility, stability and low production costs have fuelled global demand for plastic products. As a result of the increase in production, the amount of plastic waste has also increased. Marine plastic debris arises from land disposal, wastewater treatment processes, construction, disposal at sea and the breakdown of in-use plastic item, such as fishing gears. Once at sea plastics can be redistributed by ocean currents and the environmental conditions caused them to be weathered and/or colonised by organisms. These processes lead to a breakdown of plastic items into smaller fragments, changing their properties (more dense, fast sinking rate, etc.) leading them to the seafloor. Therefore, ocean sediments are regarded as the ultimate destination for small plastic particles. Microplastics (<1 mm) besides the degradation of larger plastic items, also include those items which are produced in the micro-size range such as micro-pellets and powers. It is crucial to understand which are the main pattern of distribution to assess which environments could be mainly influenced by the occurrence of plastic debris. This study presents the record of plastic contamination in sediments samples from three different benthic domains, all related to Norwegian waters including the first observation of microplastic contamination in the Kveithola Trough. Three cores were sampled from the Oslofjord, in locations characterised by almost shallow waters (~100 m); two sediment cores were sampled from deep environments (1320 – 1650 m) in the North-eastern slope of the Greenland Sea close to the Svalbard archipelago; and finally, two from Kveithola, a trough engraved on the margin of the shallow Barents Sea bank (230 – 340 m). Plastic particles were detected in every core analysed using a high-density separation approach (NaI, 1.8 g cm-3). Each plastic particle was described based on its morphology (size, shape, colour) under an optical microscope. Further, the polymeric origin of particles was chemically confirmed using Attenuated Total ...